The Effects of Prenatal Diagnosis on the Interaction of the Mother–Infant Dyad: A Longitudinal Study of Prenatal Care in the First Year of Life - de Souza, Vera Cristina Alexandre; Parlato-Oliveira, Erika; Anchieta, Lêni Márcia; Machado, Alexei Manso Correa; Savelon, Sylvie Viaux (Frontiers in Psychology, 2022)
Introduction: Mother-child interactions during the first years of life have a significant impact on the emotional and cognitive development of the child. In this work, we study how a prenatal diagnosis of malformation may affect maternal representations and the quality of these early interactions. To this end, we conduct a longitudinal observational study of mother-child interactions from the gestational stage until the baby completes twelve months of age. Participants and methods: We recruited 250 pregnant women from a local university hospital. Among them, 50 mother-infant dyads participated in all stages of the study. The study group consists of 25 pregnant women with fetuses with some structural alteration and the control group consists of 25 pregnant women with fetuses without structural anomalies. We collected obstetric and sociodemographic data, pregnancy outcomes, anxiety and depressive state using the Covi and Raskin scales. We video-recorded the mother-infant interactions during several stages: when the child was a newborn and when the child was two, four, six, nine and twelve months of age. We then measured the quality of these interactions using the Coding Interactive Behavior (CIB) scales to analyse three distinct moments: (1) when they play with a toy, (2) when the mother sings a song and (3) when only the mother’s speech is involved. Results: In the gestational phase, anxiety and depression scores were significantly higher for the study group. In the postnatal phase, we found significant differences between the groups with respect to CIB scales: the study group presented significantly higher values of maternal sensitivity, at the baby’s six and nine months of age, of involvement, at the baby’s nine and twelve months of age, and of dyadic reciprocity, at the baby's six, nine and twelve months of age; the control group presented significantly higher values of baby's retraction, at the baby's six months of age, and of negative states, at the baby’s six, nine and twelve months of age. Conclusion: The prenatal diagnosis did not compromise the type of maternal representation, increased maternal sensitivity and had a positive effect on the quality of mother-infant interaction during the first year of life.